Morphosemantic Analysis of the Pseudonyms of Disc Jockeys (D.J.) in the City of Ouagadougou: The DJ's Pseudonym Between Ostentation and the Quest for Celebrity - OUALI, Malpoa Laetitia; DAÏLA, Béli Mathieu; NANEMA, Michel (International Journal of Language and Literary Studies, 2025)
This article focuses on the pseudonyms used by a category of artists called disc jockeys (D.J.). It aims to analyze the sociolinguistic characteristics of these pseudonyms and the linguistic dynamics that emerge from them. The analysis from a morphological and semantic perspective revealed the nature, form, and linguistic origin of these designations. The pseudonyms of disc jockeys are intended both to distinguish the bearers and to increase their popularity. The pseudonyms refer to the names of film actors, music artists, and political figures. The writing of this article uses the tools of sociolinguistics through a qualitative method. Cultural actors, nightclub owners, and disc jockeys were interviewed about pseudonyms and their ostentatious characteristics through an interview guide.